2021
DOI: 10.1167/iovs.62.9.26
|View full text |Cite
|
Sign up to set email alerts
|

Choroidal and Retinal Thickness and Axial Eye Elongation in Chinese Junior Students

Abstract: To explore the associations between macular choroidal and retinal thickness and axial elongation in non-myopic and myopic junior students. METHODS.In this school-based longitudinal observational study, axial length was measured by optical low-coherence reflectometry, and choroidal thickness and retinal thickness were measured by spectral-domain optical coherence tomography. Myopia was defined as non-cycloplegic objective spherical equivalent refraction ≤ −0.50 diopters. Structural equation modeling and multipl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 52 publications
4
20
0
Order By: Relevance
“…Last but not the least, the coefficients between choroidal thickness and change in AL were relatively small, despite the p values were significant. The results were in accordance with previous studies, [40][41][42] however, we also need to be cautious that the relationship between choroidal thinning and AL elongation is not absolute, and can be dissociated under some certain conditions such as brief episodes of lens wear. [43][44][45]…”
Section: Discussionsupporting
confidence: 91%
“…Last but not the least, the coefficients between choroidal thickness and change in AL were relatively small, despite the p values were significant. The results were in accordance with previous studies, [40][41][42] however, we also need to be cautious that the relationship between choroidal thinning and AL elongation is not absolute, and can be dissociated under some certain conditions such as brief episodes of lens wear. [43][44][45]…”
Section: Discussionsupporting
confidence: 91%
“…A previous study reported that choroidal thinning during accommodation is most pronounced within the temporal region but not the subfoveal region. 26 Harb et al 27 found thinner choroids in eyes with longer axial lengths at all locations except at 2250 µm temporal to the fovea. Although the measurement of choroidal thickness in these studies was limited to a 3-mm B-scan around the fovea, the results showed regional differences in choroidal thinning in eyes with myopia.…”
Section: Discussionmentioning
confidence: 93%
“…Although the measurement of choroidal thickness in these studies was limited to a 3-mm B-scan around the fovea, the results showed regional differences in choroidal thinning in eyes with myopia. 26 , 27 According to the most widely accepted theory of pathogenesis, the mechanical stretching caused by axial elongation results in choroidal thinning. Tian et al 26 and Vincent et al 28 reported that choroidal thinning related to myopia is only partially explained by simple passive choroidal thinning with axial elongation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Blurred vision during hyperglycemia has been the consequence of temporary refractive alterations produced by lens modifications ( 104 ), although it might also be caused by retinal abnormalities. The degree of retinal thickness is connected with visual acuity ( 105 , 106 ), and can also cause changes in the length of the eye axis, which can result in refractive errors ( 104 ). As a result, we may speculate about the role of IF in altering changes in certain ocular biological parameters or reducing refractive errors in diabetic and hyperglycemic conditions through blood glucose control.…”
Section: Intermittent Fasting and Eye Diseasementioning
confidence: 99%